The Forming Factors of Business Field Diversification Decision in Family Business Enterprise in Indonesia - Andy Sanjoko; Damelina B. Tambunan (Universitas Medan Area, 2024)
Family Business Enterprise (FBE) has unique matters and is different from non-FBE in general such as succession issues, leadership transfer, internal conflicts, and decreasing company performance. One of the strategies that can be applied is to diversify the business as done by large FBEs in Indonesia. This study aims to determine what factors shape business diversification decisions at FBEs in Indonesia. The method used is a quantitative approach using EFA (Exploratory Factor Analysis) and distributing questionnaires to 183 respondents who have been obtained through purposive sampling. The results showed, that from 8 factors 7 factors shape the decision to verify FBE in Indonesia, which are resources and leader's characteristics, stimulus, business competition, business environment, internal conditions, potential opportunities, and market trends. The resources and leader's characteristics factor dominate the verification decision, especially for different business fields (conglomerates). Meanwhile, the market trend, which was originally an indicator of the market factor, turned into one of the main factors in making verified decisions